Pengaruh Religiusitas Dan Pengetahuan Produk Bank Syariah Terhadap Keputusan Masyarakat Menabung Di Bank Syariah (Studi Kasus Masyarakat Kec. Air Joman) - Harahap, Nur Rizky Ardianty; Hasanah, Uswah (LPPM Universitas Labuhanbatu, 2023)
This study aims to examine and determine the effect of religiosity and product knowledge of Islamic banks on people's decisions to save in Islamic banks. Research Methods This thesis is a type of quantitative research. This study uses one independent variable and one dependent variable. The independent variables in this study are religiosity and product knowledge, while the dependent variable in this study is people's interest in saving in Islamic banks. The data collection technique in this study was in the form of questionnaires distributed to 100 respondents. In analyzing the data, the researcher uses data analysis with several steps to test the validity of the data, test the reliability, test the simple regression and test the hypothesis. The results of the hypothesis test carried out show that the significance value for the influence of religiosity (X1) and product knowledge (X2) on people's decisions to save in Islamic banks (Y) is 0.000 <0.05 and fcount 589.875 > ftable value 3.090, so this proves that significantly Simultaneously, religiosity (X1), product knowledge (X2) has a positive and significant effect on people's decisions to save in Islamic banks (Y).